Integration von Zuwanderern. Indikatoren 2015. - (:unkn) unknown (My University, 2015)
Die Publikation ist die erste umfassende, auf Ebene aller EU- und OECD-Länder durchgeführte internationale Vergleichsstudie der Situation der Zuwanderer und ihrer Kinder. Sie ist das Ergebnis einer Kooperation zwischen der Europäischen Kommission (Generaldirektion Migration und Inneres) und der OECD-Abteilung Internationale Migration mit dem Ziel eines regelmäßigen Monitoring vergleichbarer Integrationsindikatoren in den EU- und OECD-Ländern.

In 2012, one in ten people living in the EU and OECD areas was born abroad, totalling around 115 million immigrants in the OECD and 52 million in the EU, of which 33.5 million were from non.EU countries. In both the EU and the OECD, the immigrant population has grown by more than 30% since 2000. This report presents a detailed international comparison of the outcomes of immigrants and their children in all EU and OECD countries, in the areas of labour market, education, income, housing, health, civic engagement, and social cohesion, accompanied by comprehensive background information.
Keywords: Einwanderung; Bevölkerungsentwicklung; Integration; Ausländerpolitik; Migration; Ländervergleich